Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Answer:
(4, 1 )
Step-by-step explanation:
x + 6y = 10 → (1)
x + 5y = 9 → (2)
subtract (2) from (1) term by term to eliminate x
0 + y = 1
y = 1
substitute y = 1 into either of the 2 equations and solve for x
substituting into (1)
x + 6(1) = 10
x + 6 = 10 ( subtract 6 from both sides )
x = 4
solution is (4, 1 )
We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.